The Relationship Between Duration of Contraceptive Implant Use and Changes in Body Weight: A Longitudinal Study - Novitasari, Bella; Anastasya, Riska (Trigin Institute, 2025)
This study examines the relationship between the duration of contraceptive implant use and changes in body weight, addressing a common concern among users of hormonal contraception. Conducted as a longitudinal observational study, the research involved 150 participants aged 18-45 who were monitored over two years. Data on body weight, lifestyle factors, and implant usage duration were collected through regular follow-ups and analyzed using statistical techniques to identify correlations and trends. The findings revealed a moderate positive correlation between the length of implant use and weight gain, with participants experiencing an average increase of 3.8 kg over 24 months. Key contributing factors included sedentary lifestyles, higher caloric intake, and younger age. The study also identified challenges in isolating the effects of implants from other variables influencing weight, as well as potential biases in self-reported data on diet and physical activity. The results underscore the importance of personalized counseling by healthcare providers to address weight-related side effects and encourage healthy lifestyle habits among implant users. While the study confirms existing evidence of progressive weight gain associated with contraceptive implants, it also highlights the need for further research to refine the understanding of this relationship and develop strategies for mitigating side effects. This research contributes to informed decision-making for both users and healthcare professionals, promoting better reproductive health outcomes.